2000 Families: identifying the research potential of an origins-of migration studies - Ayse Guveli; Harry Ganzeboom; Helen Baykara-Krumme; Lucinda Platt; Şebnem Eroğlu; Niels Spierings; Sait Bayrakdar; Efe K Sozeri; Bernhard Nauck (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Despite extensive recent advances in the empirical and theoretical study of migration, certain critical areas in the analysis of European migration remain relatively underdeveloped both theoretically and empirically. Specifically, we lack studies that both incorporate an origin comparison and trace processes of intergenerational transmission across migrants over multiple generations and incorporating family migration trajectories. This paper outlines the development, data and design of such a study, the 2000 Families study, framed within a theoretical perspective of 'dissimilation' from origins and over generations. We term the study an origins-of-migration study, in that it captures the country of origin, the family origins and potentially the originating causes of migration processes and outcomes. The resulting data comprised nearly 2,000 migrant and non-migrant Turkish families with members across three or more generations, covering. 50,000 individuals. We reflect on the potential of this study for migration research.
Keywords: 330; Migration; Europe; Turkey; dissimilation; intergenerational transmission; originsof-migration study